Rancang Bangun Pembangkit Listrik Skala Kecil Berbasis Mesin Stirling - Dewi, Rany Puspita; Arnandi, Wandi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
Electricity needs has increased along with the increasing of people. Majority comes from fossil energy. Utilization of biomass energy from rice husk became prospective solution to fulfill electricity needs now days. It can be seen from the rice husk potential in Indonesia at 2015 for about 15,079,568 tons. Rice husk can be used to generate the electricity by using stirling engine. The research aims to study the effect of combustion air flow to the efficiency of biomass power plants based on stirling engine. It was to know the optimum condition the power plant. Research was done by experimental method with design and test the prototype of biomass power plant integrated with downdraft gasifier and alternator. Test was done by variating combustion air flow with open valve angle about 30°; 45°; and 60°. The highest temperature was obtained at an open valve angle 30° and with stirring.